A Study on Knowledge and Adoption of Dairy Farmers about Animal Husbandry Practices - Shakya, S.K.; Badodiya, S.K.; Nagayach, U.N. (Indian Journal of Extension Education, 2019)
Livestock sector has played a crucial role in improving socio-economic status of farmers. The study was conducted purposively in Morar Block of Gwalior district with120 dairy farmers. The data collected with the help of pre-tested interview schedule shows that more than half of the milk producers had medium level of knowledge regarding improved animal husbandry practices. About 58.00 per cent of the milk producer had medium level of adoption of improved animal husbandry practices.
Keywords: Adoption; Animal husbandry practices; Knowledge